2008
DOI: 10.1097/pcc.0b013e3181849dfe
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the factors associated with hypercoagulability in the pediatric patients at a tertiary care children’s hospital*

Abstract: The population at our institution is reflective of the previously reported standards for the genetic predispositions toward thrombosis. Although older age is associated with a lower incidence of thrombosis, the presence of a central venous access device is detrimental. Accumulation of factors results in an increased risk of thrombosis. This article suggests that when inserting a central venous access device, consideration of a hypercoagulation workup should occur. Those with any two or more risk factors, genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This study found a significant statistical association ( P = 0.038) between shortened PT or aPTT results and clinical evidence of hypercoagulability such as thrombosis of intravenous or arterial catheters, suspect PTE and vessel thrombosis indicating that PT and aPTT values may be beneficial in the assessment of hypercoagulability. Similarly, an increased risk of venous thrombosis has been associated with central venous catheter placement in people with underlying diseases such as cancer and infection . In people, shortened aPTT value was associated with increased prothrombin fragments and thrombin generation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found a significant statistical association ( P = 0.038) between shortened PT or aPTT results and clinical evidence of hypercoagulability such as thrombosis of intravenous or arterial catheters, suspect PTE and vessel thrombosis indicating that PT and aPTT values may be beneficial in the assessment of hypercoagulability. Similarly, an increased risk of venous thrombosis has been associated with central venous catheter placement in people with underlying diseases such as cancer and infection . In people, shortened aPTT value was associated with increased prothrombin fragments and thrombin generation .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an increased risk of venous thrombosis has been associated with central venous catheter placement in people with underlying diseases such as cancer and infection. [30][31][32] In people, shortened aPTT value was associated with increased prothrombin fragments and thrombin generation. 18 People with acute coronary events secondary to arterial thrombosis had significantly shorter aPTT values compared to patients with stable coronary disease and for every 0.013 seconds of aPTT shortening, fVIII activity level increased by 1%.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The evidence for these therapies in pediatrics is limited and inconsistent. [10][11][12] Similarly, the lack of uniformity of anticoagulant use in the pediatric critical illness, as illustrated by the confusing array of dosages, routes, and methods of administration, led us to attempt to characterize the practices and opinions of the pediatric critical care community concerning the use of CVC-associated heparin prophylaxis (HP).…”
Section: Introductionmentioning
confidence: 99%
“…These disorders act synergistically with increased age, recent surgery, bed rest, trauma, pregnancy, estrogen therapy, inflammatory diseases, uremia, cancer, obesity, metabolic syndrome, varicosities and prior venous thromboembolic disease (TED) to further increase the risk of TED for upper and lower extremities, for children and adults [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%